Five new species of Ocotea (lauraceae) from Bahia, Brazil - De Moraes, Pedro Luís Rodrigue [UNESP]; Van Der Werff, Henk (Harvard University Botany Libraries, 2012)
Five South-American species of the genus Ocotea from Bahia, Brazil, are described and illustrated. The new species are Ocotea adamantina, O. rohweri, O. sperata, O. thinicola, and O. vegrandis. Their relationships within the genus are discussed. © President and Fellows of Harvard College, 2011.
Keywords: Bahia; Brazil; Lauraceae; New species; Ocotea